EFEKTIFITAS MODEL PEMBELAJARAN COOPERATIVE LEARNING, TIPE GROUP INVESTIGATION DALAM PEMBELAJARAN IPAS MATERI GAYA DAN ENERGI TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V DI SD INPRES AWAALAH - Lasai, Shilpa Novia Gardenia; Daik, Triznawasti Y.; Kabbi, Astina Y. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Merdeka Curriculum requires IPAS instruction that fosters students’ active engagement, critical thinking skills, and problem-solving skills through meaningful learning experiences. However, findings from observations at SD Inpres Awaalah indicate that the learning process remains teacher-centered and relies on conventional methods, resulting in fifth-grade students’ learning outcomes failing to meet the established Learning Objective Achievement Criteria (KKTP). This study was conducted to examine the effectiveness of implementing the Group Investigation type of Cooperative Learning model in improving IPAS learning outcomes on the topic of force and energy. The method used was a quantitative quasi-experimental approach with a Nonequivalent Control Group design. The study involved two sample groups: Class VA as the control group and Class VB as the experimental group, each consisting of 17 students. Data were collected through pretest and posttest instruments, as well as student response questionnaires, and were then analyzed using normality tests, homogeneity tests, and an independent samples t-test using SPSS version 22. The findings indicate that the average posttest score of the experimental group (90.88) significantly exceeded that of the control group (60.00). The independent samples t-test yielded a p-value of 0.001 (<0.05), with a calculated t-value of 4.421 exceeding the critical t-value of 2.037, confirming the existence of a statistically significant difference in learning outcomes between the two groups. In addition, the rate of positive responses from students in the experimental group reached 85%, which falls into the “very good” category. Based on these results, it can be concluded that the application of the Group Investigation type of Cooperative Learning model proved effective in improving students’ IPAS learning outcomes on the topic of force and energy.